HISTÓRIA DA EDUCAÇÃO NA GUINÉ-BISSAU: ANÁLISE DO PROJETO EDUCATIVO DO PAIGC NO PERÍODO DA LUTA DA LIBERTAÇÃO NACIONAL (1963-1973) - COSTA, ADENAUER MARCOS DA (2023)
Before the Portuguese invasion in the current Guinea-Bissau, this territory was populated by several ethnic groups that had their social, political, cultural, and educational organizations, among other norms of coexistence and ways of living. These ethnic groups that made up the State of Guinea-Bissau had a very rich education based on the oral transmission of knowledge, in which positive values were passed on from the elders to the youngsters, from generation to generation. It is exactly the presence of this cutout, still in force today, that became the focus of this research. The central scope was to analyze the records of the history of education in Guinea-Bissau from three distinct educational perspectives: i) the educational perspective in the oral tradition, from the African bibliographic production on the educational process of the Balanta ethnic group; ii) from the African bibliographic production, which presents the fundamental features of the colonial schooling process in Guinea-Bissau; iii) and the PAIGC educational process during the period of the national liberation struggle (1963-1973). The education that the Portuguese implemented was based on the Western reality, directed exclusively to the children of traditional chiefs and to the assimilated (individuals who assimilated to European culture and those who professed the Catholic faith, which left a significant number of Guineans out of colonial education). Due to this exclusion from education, the African Party for the Independence of Guinea and Cape Verde (PAIGC, acronym in Portuguese) created its own educational project with the intention of safeguarding local cultures and their values and training future cadres, with the mission of developing the two countries (Guinea and Cape Verde) when they became independent and free from colonial oppression. The educational model implemented by the PAIGC in the liberated zones sought to recapture what was important in the experience of traditional Guinean society without disregarding the knowledge of the elders, the griot, the healers, and other types of knowledge. To answer the problem of this work, we used a post-colonial theoretical perspective aligned with the cultural, philosophical, artistic and literary history left by colonialism in both colonized and colonizers countries. In order to undertake the proposed analysis, this research was characterized, firstly, as bibliographical, because it resorted to sources constituted by already elaborated material, such as books and scientific articles. In regards to the research's methodological procedure, the phenomenological method was used to better understand the participants' experiences and to analyze the data obtained through the interviews. It was possible, from this approach, to listen to the lived experiences of the interviewed subjects and rescue the memory of their access to formal education and the notes they studied during their schooling periods. Within its project, the PAIGC did not rule out the possibility of forming a "New Man". Amílcar Cabral insisted a lot on the notion of the "New Man", that is, a man different from the one who was formed in the colonial school with European principles and culture. In this logic of thought, the school would be an alternative to educate citizens, form the "New Man" and thinkers of the future nation.